Criteria For Selecting And Organizing Grammatical Content In Umm Al-Qura University Series For Teaching Arabic To Non-Native Speakers/ معايير اختيار المحتوى النحوي وتنظيمه في سلسلة جامعة أم القرى لتعليم اللغة العربية لغير الناطقين بها - Almalki, Mohammed Abdullah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This research attempts to reveal the criteria for selecting and organizing grammatical content in the Umm Al-Qura University series for teaching Arabic to non-native speakers, considering it a model worthy of study as it is the most recent series prepared by a group of professors and experts from the Institute of Teaching Arabic to Non-Native Speakers at Umm Al-Qura University. Hence, the research gains its importance in shedding light on one aspect of language teaching: the grammatical aspect in this important educational series that has enriched the field of language teaching by benefiting from previous efforts and what has been new in teaching foreign languages. The research problem is summarized in the multiplicity and diversity of visions in organizing grammatical content in theory and application, as well as the need for modern systems in language teaching to crystallize an educational curriculum that considers the significant development in societies. The research is based on the descriptive analytical approach to the contents and objectives of the grammatical content in the series, which amounts to eight books allocated to students in the Language Qualification Diploma Program. The research included an introduction and several axes related to the foundations for selecting and organizing grammatical content. The research revealed that the series considers the criteria for selecting and organizing content according to modern linguistic and educational visions. It considered the distinction between academic and scientific grammar and the logical sequence, such as moving from the general to the specific, from the simple to the complex, and from the easy to the difficult. It also considers the gradation level, continuity, sequence, and integration. Its communicative activities also took into account the inclusion of grammatical content and the enhancement of its skills